PEMANFAATAN PISANG TANDUK (Musa x paradisiaca L.) DAN SIRSAK (Annona muricate L.) DALAM PEMBUATAN SELAI LEMBARAN SUMBER SERAT: Utilization of Horn Plantain (Musa x paradisiaca L.) and Soursop (Annona muricate L.) in The of Making Fiber Source Sheeted Jam - Eveline Eveline; Angelina Cornelia Hindarto (Pro Food, 2020)
ABSTRACT Horn plantain and soursop are horticultural products of climacteric fruits that contain high nutrition and fiber, but have a relatively short shelf life after harvest. One solution so that both of them can still be consumed by maintaining their nutritional and fiber content is making sheeted jam. This study aims to determine the ratio of puree horn plantain and soursop, and to determine the ratio of carrageenan:konjac hydrocolloid and the concentration of hydrocolloid in the making of fiber source sheet jam. Initially, horn plantain and soursop were made into a puree (ratio of horn banana puree : soursop = 1:0, 3:1, 1:1, 1:3, and 0:1). The 1:3 ratio was chosen as the best ratio (fiber content of 5.82%) and was subsequently used in the determination of the hydrocolloid ratio of carrageenan: konjac (1:0, 1:1, and 1:2) and the concentration of hydrocolloid (1.0; 1.5; and 2%). A ratio of 1:1 with a concentration of 2% hydrocolloid produces the best sheeted jam based on dietary fiber content of 5.60%; syneresis 0.28%; pH 3.43-3.62; total dissolved solids (TDS) 33.73-34.87° Brix; hardness 671,74 g; water 45.79%; ash 0.08%; fat 0.05%; protein 0.35%; carbohydrates (by difference) 53.73%; and still accepted by consumers with the overall hedonic value (4.91 on a scale of 7.00 [neutral]). Keywords: fibre; hidrocoloid, jam; plantain; soursop ABSTRAK Pisang tanduk dan sirsak merupakan produk hortikultura buah-buahan klimakterik yang mengandung gizi dan serat tingi, namun memiliki waktu simpan relatif singkat setelah panen. Salah satu solusi agar keduanya tetap dapat dikonsumsi dengan mempertahankan kandungan gizi dan seratnya adalah pembuatan selai lembaran. Penelitian ini bertujuan untuk menentukan rasio puree pisang tanduk dan sirsak, serta menentukan rasio hidrokoloid karagenan:konjac dan konsentasi hidrokoloid dalam pembuatan selai lembaran sumber serat. Awalnya, pisang tanduk dan sirsak dijadikan puree (rasio puree pisang tanduk:sirsak = 1:0, 3:1, 1:1, 1:3, dan 0:1). Rasio 1:3 terpilih sebagai rasio terbaik (kandungan serat 5,82%) dan selanjunya digunakan dalam penentuan rasio hidrokoloid karagenan:konjac (1:0, 1:1, dan 1:2) serta konsentrasi hidrokoloid (1,0; 1,5; dan 2%). Rasio 1:1 dengan konsentrasi hidrokoloid 2% menghasilkan selai lembaran terbaik berdasarkan kandungan serat pangan sebesar 5,60%; sineresis 0,28%; pH 3,43-3,62; total padatan terlarut (TPT) 33,73-34,87°Brix; hardness 671,74 g; air 45,79%; abu 0,08%; lemak 0,05%; protein 0,35%; karbohidrat (by difference) 53,73%; dan masih diterima konsumen dengan nilai hedonik keseluruhan (4,91 dari skala 7,00 [netral]). Kata kunci: hidrokoloid, pisang, serat, selai, sirsak